Źwierzę w Kronice, to jest historyi świata Marcina Bielskiego (1564) - Kozaryn, Dorota (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The aim of the article is to show how the lexeme źwierzę (animal) functions in the first Polish-language history of the world, published for the third time in 1564 and edited by Marcin Bielski, entitled Kronika, to jest historyja świata (The Chronicle, That Is the History of the World). The analysis shows that the word źwierzę and its derivatives appear in the Kronika when naming fauna that both actually existed and was legendary; they are used by Bielski as generalizing names (hyperonyms) and individual names; their inflectional forms reflect the norm of the time. It is necessary to emphasize the relationship between the human and animal worlds that emerges from the presented remarks, indicating a partial departure from anthropomorphism, and the fact that the meaning of the word źwierzę and its derivatives is limited primarily to mammals, which in turn is consistent with the linguistic image of animals characteristic of general Polish and is still in use today.